2012
DOI: 10.1136/archdischild-2011-301089
|View full text |Cite
|
Sign up to set email alerts
|

Managing bone and joint infection in children

Abstract: There is little high quality evidence on which to base the management of bone and joint infections in children. This pragmatic practice note aims to provide a consensus framework of best current practice prior to the availability of data from large national randomised controlled trials. For straightforward infection in previously normal children, recent trends suggest that shorter length of intravenous therapy with switch to oral treatment is acceptable, although this is not the case for the management of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 65 publications
(59 reference statements)
4
92
0
4
Order By: Relevance
“…Eleven samples were fluids including pus, two were blood cultures and one was tissue. Although a higher frequency than previously reported, 1 this study was conducted during the time of a reported outbreak of GAS infections nationwide in the UK. 70 Two patients (ages 5.2 years and 0.8 months) were found to have OM/SA due to S. pneumoniae.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Eleven samples were fluids including pus, two were blood cultures and one was tissue. Although a higher frequency than previously reported, 1 this study was conducted during the time of a reported outbreak of GAS infections nationwide in the UK. 70 Two patients (ages 5.2 years and 0.8 months) were found to have OM/SA due to S. pneumoniae.…”
mentioning
confidence: 67%
“…1 As no children aged ≤ 2 months were included in this microbiology substudy, this finding is not unexpected as GBS infections are rare in older infants and children.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In the case of unifocal osteomyelitis continuation of treatment for six weeks and in the case of complex disease, defined as multifocal, significant bone destruction, resistant unusual pathogen, septic shock, continuation for more than six weeks to months might be required. Antimicrobial treatment is frequently administered intravenously for two to three weeks and then switched to oral medication [52]. Surgery is indicated to drain acute abscesses or when no improvement is achieved with antibiotic treatment.…”
Section: Treatmentmentioning
confidence: 99%